(untitled) (American Journal of Technology and Applied Sciences, 2024)
Sovereign wealth funds (SWFs) have over 11.83 trillion in assets under management as of Octaber 2023. Most of these 176 funds are sponsored by non-Western countries and their growth has made SWFs important international investors, particularly in private equity funding. We first define SWFs, then discuss their evolution into today’s categories of stabilization, savings, and development/strategic funds. We discuss the documented importance of SWF funding sources – oil sales revenues versus excess reserves from export earnings – and summarize the empirical literature studying how SWFs allocate funds geographically and across asset classes.